459 Sectoral differences in workplace ill-treatment in ireland. (24th April 2018) - Hogan, V; Hodgins, M; Pursell, L; McCurtain, S; Mannix-McNamara, P; Lewis, D
Abstract : Introduction: It is well known that bullying varies by sector (Fervre, et al., 2012). However, national Irish data on workplace bullying and mistreatment in the workplace predates the economic recession, therefore, may no longer reflect current trends in Ireland. Therefore, this study aimed to establish the prevalence of workplace mistreatment in a nationally representative sample of Irish employees and to examine sectoral patterns in order to identify higher risk sectors. Methods: The data for this study comes from the first Irish Workplace Behaviour Study (IWBS), which replicated the British Workplace Behaviour Survey conducted in 2008 (BWBS) (Fervre, Lewis, Robinson & Jones, 2011). This Irish study consisted of a cross-sectional study of a national probability sample of employees. Survey data was collected through the use of an Omnibus Survey of the Irish population. The sample consisted of 1764 people aged 18 and over. A response rate of 74% was achieved. Data analysis was conducted using SPSS Version 22. Result: Ill-treatment across sectors were compared using a three factor structure comprised of unreasonable management, incivility and disrespect and the experience of violence or injury. In addition, the prevalence of experience, witnessing and perpetration of mistreatment across sectors is presented. The public sector and large organisations are identified as higher risk sectors within Ireland. Discussion: Prevalence rates of workplace ill-treatment are examined with reference to both national and international comparative findings. Sectoral differences in prevalence rates of workplace mistreatment indicate increased risk for certain working populations and have implications for the management of mental health and well-being.